Recovery of Endothelial Cell Prostacyclin Production after Inhibition by Low Doses of Aspirin - Jaffe, Eric A. (1979)
Endothelial cells synthesize prostacyclin (PGI(2)), an unstable prostaglandin that inhibits platelet aggregation and serotonin release. Because cyclooxygenase, which is necessary for synthesis of PGI(2), is inactivated by aspirin, we examined the effect of aspirin on PGI(2) production by cultured human endothelial cells. Endothelial cells synthesize PGI(2) (20.1±7.2 ng/10(6) cells, mean±SD) when stimulated with 20 μM sodium arachidonate for 2 min. PGI(2) production is inhibited by low-dose aspirin (5 μM); the t(½) of inactivation is 6.0±1.3 min (mean±SEM, n = 3). Thus, endothelial cell cyclooxygenase is as sensitive to aspirin as the enzyme in platelets. After 1 h incubation with aspirin, endothelial cell PGI(2) production was inhibited 50% by 2.1±0.4 μM aspirin and was inhibited 90% by 6.2±0.9 μM aspirin (mean±SEM, n = 4). When endothelial cells were incubated with 100 μM aspirin, washed, and recultured, their ability to synthesize PGI(2) returned to control levels in 35.6±1.0 h (mean±SEM, n = 4). Recovery of endothelial PGI(2) production after aspirin depended on de novo protein synthesis because treatment with cycloheximide (3 μg/ml) inhibited recovery by 92%. These results indicate that although endothelial cell cyclooxygenase in vitro is inhibited by low concentrations of aspirin, endothelial cells rapidly resynthesize their cyclooxygenase after the aspirin is removed. This rapid resynthesis of cyclooxygenase lessens the likelihood that aspirin used in clinical doses promotes thrombosis.